Evaluation of TMPA 3B42 daily precipitation estimates of tropical cyclone rainfall over Australia. Issue 21 (8th November 2013) - Chen, Yingjun; Ebert, Elizabeth E.; Walsh, Kevin J. E.; Davidson, Noel E.
<x xml:space="preserve">Abstract</x> [1] Heavy rain from tropical cyclone (TC) landfall has extensive impacts on human life and society. Its estimation is subject to considerable uncertainty, especially in Australian tropical regions. In this study we evaluate the Tropical Rainfall Measuring Mission (TRMM) Multi‐satellite Precipitation Analysis (TMPA) 3B42 rainfall estimates in landfalling TCs over Australia. A high‐quality gauge‐based gridded rainfall product from the Australian Water Availability Project (AWAP) is utilized as reference data. The overall characteristics of TMPA 3B42 estimates are measured by mean rain rate, correlation coefficient, relative bias, relative root‐mean‐square error, and empirical orthogonal function analysis on both AWAP and TMPA 3B42. These comparisons show good correspondence over space and time between TMPA 3B42 and AWAP analysis for rainfall at TC landfall over Australia. The results also show that TMPA 3B42 generally overestimates TC rain for low rain rate but underestimates TC rain at high rain rate. TC intensity, location, terrain, and TC seasons all have impacts on TMPA 3B42's detection skill. For TC heavy rain, TMPA 3B42 shows better agreement with AWAP during more intense TCs (CAT3–5), in the eyewall as opposed to the rain bands, in the tropics as opposed to the subtropics, and in late TC seasons as opposed to early and peak TC seasons. Finally, a case study for TC Yasi (2011) is chosen to illustrate TMPA 3B42's ability to estimate TC landfall rainfall over Australia. Even though the performance of TMPA 3B42 can vary from case to case, TMPA 3B42 has a high correlation coefficient with AWAP and achieves good skill scores in most cases.